Moisture air-oven methods [videorecording] - Ikeda, Henry S. (St. Paul, Minn. American Association of Cereal Chemists, 1985)
Demonstrates methods to measure moisture levels in grains and legumes.
VHS
Keywords: Food -- Moisture; Cereals products